Pengaruh Pengalaman Pemasaran terhadap Loyalitas Pelanggan Rumah Kecantikan dr Rina dengan Kepuasaan sebagai Variabel Intervening - Santika, Dinda; Harahap, Hastuti Handayani; Sarwoto, Sarwoto (Sekolah Tinggi Ilmu Ekonomi Bina karya, 2022)
Marketing theories become the basic theory, especially the theory of consumer behavior. The aim of the study is to show answers to the research hypothesis: marketing experience influences customer satisfaction with a T-statistic value of 19.593 and customer loyalty with a T-statistic value of 2.676. Customer loyalty is influenced by customer satisfaction, the value of the T-statistic is equal to 3.245 and customer satisfaction is the intervening variable between the effect of marketing experience on customer loyalty with a coefficient value of 0.4122. The research was conducted on 97 respondents as well as being the research sample. Data processing using SPSS 25.0 software